Metodologia identyfikacji i badania klastrów regionalnych - Zbadyński, Mariusz (Methodology of the Identification and Research into Regional Clusters, 2006)
The majority of the literature on regional clusters focuses on the actual definition of a cluster. The very basic definition of an industry cluster is "geographical concentrations of industries that gain performance advantages through co-location". The varying definitions of industry clusters helps explain the differing arguments regarding the methodology to identify clusters. One of the common approaches to identifying clusters is based on quantitative techniques, including location quotients and input-output (I-O) analyses. The quantitative approach towards identifying industry clusters is generally regarded as a critical component of a cluster analysis. This type of analysis will provide an initial tool for identifying potential clusters and will indicate the relative presence of different industries in the local region. There is a general consensus in the literature that in order to truly identify industry clusters it is necessary to conduct a qualitative analysis in addition to the quantitative analysis. The use of the qualitative analysis will both confirm the findings of the quantitative analysis, as well as help identify potential industry clusters that may have been overlooked by the conventional data analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 214-221